Studies on the Solvation Behaviour of Ammonium Citrate in Aqueous and Partial Aqueous Media - Ishwara Bhat, J.; Manjunatha, M.N. (Asian Journal of Chemistry, 2011)
The paper deals with the study on the solvation behaviour of ammonium citrate in water and various compositions (v/v) of water + acetonitrile and water + dimethyl sulfoxide in the temperature range 283 to 313 K. The electrical conductivity data were analyzed by Kraus-Bray and Shedlovsky models of conductivity. The molar conductance at infinite dilution lmo found to decrease with increase in the amount of co-solvent indicating the increased ion-solvent interaction and solvent-solvent interactions. Association constant Ka and dissociation constant Kc have been computed in all the cases. The Ka value decreased with the increase in temperature indicating exothermic behaviour of the system. Walden product and corrected Stokes radius have been determined in all the cases of solvent mixtures. Thermodynamics of solvation such as DGs-s, DSs-s and DHs-s have also been evaluated from Born equation. These data were utilized to study the ion-solvent and solvent-solvent interactions.